2017
DOI: 10.1098/rsta.2016.0410
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen enhanced cracking studies on Fe–3wt%Si single and bi-crystal microcantilevers

Abstract: Hydrogen (H) enhanced cracking was studied in Fe-3wt%Si by means of electrochemical microcantilever bending test. It was clearly shown that the presence of H causes hydrogen embrittlement (HE) by triggering crack initiation and propagation at the notch where stress concentration is existing. Additionally, the effect of carbon content and the presence of a grain boundary (GB) in the cantilever were studied. It was shown that in the presence of H the effect of carbon atom on pinning the dislocations is reduced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…A rather limited fraction of IG type fracture indicated that grain boundaries (GBs) were not significant vulnerable places for this material when subjected to H environment. This was confirmed in a previous work by Hajilou et al [55] that the GB in Fe-3wt%Si was not a favored path for crack growth after their test of bending a micro-cantilever with a notch on a GB. They found that the crack generated from the notch would rather propagate along the direction with the highest degree of stress concentration rather than along the GB, whether in vacuum or in H environment.…”
Section: Fcgr Behavior In Airsupporting
confidence: 84%
See 1 more Smart Citation
“…A rather limited fraction of IG type fracture indicated that grain boundaries (GBs) were not significant vulnerable places for this material when subjected to H environment. This was confirmed in a previous work by Hajilou et al [55] that the GB in Fe-3wt%Si was not a favored path for crack growth after their test of bending a micro-cantilever with a notch on a GB. They found that the crack generated from the notch would rather propagate along the direction with the highest degree of stress concentration rather than along the GB, whether in vacuum or in H environment.…”
Section: Fcgr Behavior In Airsupporting
confidence: 84%
“…Since fatigue crack generally grows via ductile mechanisms even along a microstructural interface, it is reasonable to think that IG fracture is even more difficult in the FCGR testing. Furthermore, the dimension of the micro-cantilever testing in [55] can roughly present the case of a single cycle in the present FCGR testing. From these aspects, it is assumed that the GB in the investigated material has a relatively good resistance against IG cracking both in H-free and in H-charged environments.…”
Section: Fcgr Behavior In Airmentioning
confidence: 99%
“…In summary, these remarks raise the following questions: For a long time, until today, I thought that the mechanisms in zirconium and titanium were different to those in a steel or a nickel alloy. Seeing the Norwegian work presented earlier on microcantilevers in steels (see [18]), you did appear to see plasticity around a crack tip in the cantilever. That was really interesting; even in a steel you do seem to see some evidence for a localized plasticity mechanism.…”
Section: Adrian Suttonmentioning
confidence: 91%
“…To eliminate the crystallographic orientation dependency, a similar grain orientation of {101} was selected according to the orientation imaging map (OIM) of the samples. In situ electrochemical nanoindentation was performed using the Bruker TI 950 TriboIndenter system, which was integrated with a custom, three electrode miniaturized electrochemical cell [6]. The electrochemical setup consisted of counter, working, and Hg/HgSO 4 reference electrodes.…”
Section: Methodsmentioning
confidence: 99%